KOMPETENSI SDM DAN EMPLOYEE ENGAGEMENT SEBAGAI DETERMINAN KINERJA PEGAWAI DISBUDPAR TANJUNGPINANG - Melia Irmalisa; Armansyah Armansyah; Octojaya Abriyoso; Alfi Hendri; Indra Bastia Tahir (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to examine the partial and simultaneous effects of human resource competence and employee engagement on employee performance. The population in this study consisted of 64 employees, with the sample selected using purposive sampling. This study employed a quantitative research approach with a descriptive research design. Data were collected through questionnaires. The data were analyzed using multiple linear regression with SPSS Statistics 22. The results showed that human resource competence had a positive and significant effect on employee performance. Employee engagement also had a positive and significant effect on employee performance. Furthermore, human resource competence and employee engagement simultaneously had a positive and significant effect on employee performance. The contribution of human resource competence and employee engagement to employee performance was 46%, while the remaining 54% was influenced by other variables not examined in this study